2017
DOI: 10.1007/s00114-017-1476-2
|View full text |Cite
|
Sign up to set email alerts
|

Does contrast between eggshell ground and spot coloration affect egg rejection?

Abstract: Obligate avian brood parasitic species impose the costs of incubating foreign eggs and raising young upon their unrelated hosts. The most common host defence is the rejection of parasitic eggs from the nest. Both egg colours and spot patterns influence egg rejection decisions in many host species, yet no studies have explicitly examined the role of variation in spot coloration. We studied the American robin Turdus migratorius, a blue-green unspotted egg-laying host of the brown-headed cowbird Molothrus ater, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…() demonstrated robins’ rejection decisions are fine‐tuned to the gradient of natural egg colors, but robins ignore perceivable differences along artificial color gradients, a finding inconsistent with the internal “own egg versus foreign egg” template (or multiple threshold, sensu Hanley et al., ) hypothesis. Similarly, Dainson, Hauber, López, Grim, and Hanley () also found that robin egg rejection responses to egg spot coloration are likely tuned to a gradient of natural egg color patterns, where robins are more inclined to reject model eggs that have highly contrasting brown spots against a mimetic blue‐green robin egg background color.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…() demonstrated robins’ rejection decisions are fine‐tuned to the gradient of natural egg colors, but robins ignore perceivable differences along artificial color gradients, a finding inconsistent with the internal “own egg versus foreign egg” template (or multiple threshold, sensu Hanley et al., ) hypothesis. Similarly, Dainson, Hauber, López, Grim, and Hanley () also found that robin egg rejection responses to egg spot coloration are likely tuned to a gradient of natural egg color patterns, where robins are more inclined to reject model eggs that have highly contrasting brown spots against a mimetic blue‐green robin egg background color.…”
Section: Discussionmentioning
confidence: 91%
“…Here, we confirmed that discrete, categorical differences in egg background color, maculation, and size are all important cues for foreign egg recognition in robins. However, recent experimental approaches have set a new standard, using model eggs, which vary continuously rather than discretely, along natural gradients of different background colors (Hanley et al., ), as well as maculation patterns and contrasts (Dainson et al., ), and sizes and shapes (Igic et al., ). Egg rejection studies performed with continuously varying model eggs, in combination with avian visual modeling (Avilés, ; Cassey et al., ; Spottiswoode & Stevens, ), allow for estimation of perceivable differences to the host species of interest for each model egg feature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colour is not the only important feature in egg discrimination decisions. The patterns generated through eggshell maculation, including spots and lines (hereafter, spots) are also important factors as they can generate unique egg signatures [20] that provide hosts with valuable information about egg ownership (own versus foreign) [21]. Hosts with spotted eggs are generally more likely to accept spotted foreign eggs, and hosts with unspotted eggs are generally more likely to Figure 1.…”
Section: Introductionmentioning
confidence: 99%